Fabrication of Fiber Optic Magnetic Field Sensors with Ferrofluid Fe3O4/DMSO Synthesized Using the Laser Ablation Method - Ila Nur Alifah Islami; Nurul Hidayat; Muhammad Safwan bin Abdul Aziz; Arif Hidayat; Lya Rizka Herawati; ST Ulfawanti Intan Subadra; Ahmad Taufiq (Universitas Negeri Malang, 2024)
Currently, the demand for practical, highly sensitive magnetic field sensors is increasing in the industrial and medical sectors. Optical fiber magnetic field sensors are an innovation that can provide a solution to this demand. One development in optical fiber magnetic field sensors involves modifying the ferrofluid material used as the sensing material. In this study, Fe3O4/DMSO ferrofluid was synthesized using the laser ablation method. The synthesis results were then integrated with SNS (SMF – NCF – SMF) structured optical fibers to form a magnetic field sensor. The XRD results showed amorphous samples originating from glass as the Fe3O4/DMSO substrate. The FTIR spectrum confirmed the presence of Fe3O4 with the detection of octahedral and tetrahedral Fe-O functional groups. PSA characterization showed a particle size distribution of 343 nm. Furthermore, the UV-Vis spectrum absorbance showed a characteristic peak of iron oxide nanoparticles, namely at an absorption peak of 341.7 nm, and had a band gap of 2.04 eV. The performance results of the optical fiber magnetic field sensor using Fe3O4/DMSO ferrofluid show that the sensor is sensitive with a sensitivity of 1.2319e-5± 1.23477e-6a.u./mT with a linear response R2= 0.9431.